SISI GELAP SMARTPHONE: FAKTOR YANG MEMPENGARUHI KETERGANTUNGAN DAN NIAT PEMBELIAN ULANG - Antonius Satria Hadi (Universitas Ahmad Dahlan, 2021)
In this digital era, smartphones are considered a primary need in everyday life. A person's behavior that reflects the dependence on smartphones is when most of their activities were spent using a smartphone. This study aims to analyze the relationship among variables convenience,Â social influence, and social need towards the dependence on smartphones. Then, this study analyzed the relationship of dependence on smartphones towards repurchase intention. Respondents of this study were undergraduate students in Yogyakarta who are using smartphones for their daily activities. The analytical technique used in this study was structural equation modeling using LISREL 10.1 software. This study proposed four hypotheses then the result showed that all hypotheses were accepted.